Synthesis of vertical WO3 nanoarrays with different morphologies using the same protocol for enhanced photocatalytic and photoelectrocatalytic performances. Issue 38 (6th July 2021) - Li, Jingjing; Guo, Chenpeng; Li, Lihua; Gu, Yongjun; Kim, BoK.-Hee; Huang, Jinliang
Abstract : Hexagonal nanoflower WO3 arrays were synthesized via a facile hydrothermal method without the assistance of any seed layer or structure directing agent. The nanoflower WO3 has the highest photocatalytic activity for the degradation of methylene blue. Abstract : Tungsten trioxide (WO3 ) nanoarrays with different morphologies were successfully synthesized by a hydrothermal method on an FTO substrate. Various nanostructures of WO3 including nanoflakes, nanoplates, nanoflowers and nanorods were obtained by adjusting only the acidity of the precursor solution. XRD patterns confirmed that the as-prepared orthorhombic WO3 ·0.33H2 O transformed to the monoclinic WO3 phase under annealing at 500 °C. UV-Vis absorbance spectroscopy indicated that the absorption edge of WO3 nanoflowers exhibited a slight red-shift compared to other morphologies of WO3 . The obtained WO3 nanoflower arrays exhibit the highest photocurrent density and photocatalytic degradation activity towards methylene blue. Finally, the mechanism of the photocatalytic degradation of methylene blue by WO3 is discussed.